Enhanced tribological performance of PLA/CNC composites: A comparison with phenolic resin and nylon - Chia-Feng Hsieh; Shih-Chen Shi; Dieter Rahmadiawan (Journal of Engineering Researcher and Lecturer, 2024)
PLA has been developed to replace plastic because it is degradable. For more advanced applications, more research is needed on PLA. This study investigates the tribological properties of phenolic resin, nylon, and PLA/CNC composites under varying sliding distances and loads. Both phenolic resin and nylon demonstrate exceptional wear resistance and stable friction coefficients. PLA/CNC composites exhibit improved wear resistance, showing a 17% reduction in friction coefficient at a 3 wt.% CNC content. While the wear volume of PLA/CNC composites increases with sliding distance, the addition of CNC enhances PLA’s self-lubricating properties and overall wear resistance. The correlation between dissipated energy and wear volume confirms that higher CNC content significantly improves the durability of PLA. These findings suggest that CNC has considerable potential as an additive to enhance the tribological performance of PLA composites, making it a valuable material for various applications requiring superior wear resistance.